2015
DOI: 10.1097/olq.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Azithromycin-Resistant Neisseria gonorrhoeae Isolates With a Multidrug Resistance Phenotype in Fukuoka, Japan

Abstract: Over the previous 4 years, an increasing prevalence of azithromycin-resistant N. gonorrhoeae isolates with a multidrug-resistant phenotype was observed. Furthermore, the azithromycin-resistant isolates seemed to belong to 2 predominant STs. As a result, continued surveillance of gonococci resistant to antimicrobial agents, including azithromycin in Fukuoka, Japan, is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
0
23
1
1
Order By: Relevance
“…Taken together with the findings described in previous reports (22,23), our results suggest that adequate therapeutic effects cannot be obtained, even upon AZM-SR administration. Although descriptions of the effectiveness of AZM for the treatment of gonococcal urethritis have been added to the guidelines revised in 2016 (4), the decreasing susceptibility of N. gonorrhoeae to AZM has been reported in Japan (22,24). In our current study, the microbiological efficacy of a single 2-g dose of AZM-SR was 83.3%, which was lower than that previously reported (93.8%) (14).…”
Section: Discussioncontrasting
confidence: 69%
“…Taken together with the findings described in previous reports (22,23), our results suggest that adequate therapeutic effects cannot be obtained, even upon AZM-SR administration. Although descriptions of the effectiveness of AZM for the treatment of gonococcal urethritis have been added to the guidelines revised in 2016 (4), the decreasing susceptibility of N. gonorrhoeae to AZM has been reported in Japan (22,24). In our current study, the microbiological efficacy of a single 2-g dose of AZM-SR was 83.3%, which was lower than that previously reported (93.8%) (14).…”
Section: Discussioncontrasting
confidence: 69%
“…However, in countries where azithromycin is preferentially used, such as in Latin America and also Europe, the percentage of resistant isolates has rapidly risen . Internationally, azithromycin resistance has been observed to varying degrees, depending on its varying use in the treatment of gonococcal infection . In the present resistance study, the values for azithromycin resistance were very low (between 0 and 0.5 %) in the 15‐year observation period.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly a recent review recommended combined treatment with ceftriaxone and azithromycin or cefixime and azithromycin (13). However, the prevalence of azithromycin-resistant N. gonorrhoeae has been reported to be high in Fukuoka, Japan (14). The report showed that 22.6% of N. gonorrhoeae strains were azithromycin-resistant.…”
Section: Discussionmentioning
confidence: 99%